Perhubungan antara komunikasi sistem pampasan dan prestasi kerja : keadilan prosedur sebagai pembolehubah moderator - Noraida, binti Wahid (2008)
This study was conducted to examine the role of the procedural justice as a moderator in the relationship between communication about pay system and job performance. The data of this study were collected using cross-sectional method. The results of hierarchical regression analysis shown that (1) the procedural justice had not increase the effect of knowledge about pay system towards job performance; and (2) the procedural justice had increased the effect of immediate boss treatments toward job performance.